The Influence of Women’s Dual Roles on Family Economic Contribution among Working Women - Surta Tiodora Silaban (International Journal of Educational Practice and Policy, 2025)
Women's dual roles balancing household duties with professional work remain a major issue in today's discussions about education and socioeconomics. Even though more women are working outside the home, they are still often expected to take on traditional caregiving roles. This makes it hard for them to manage overlapping responsibilities. This study looks at how women handle both home and work roles, assesses the economic contributions they make to their families' well-being, and examines the link between dual roles and household stability in Indonesia. The research uses a quantitative explanatory design, selecting 20 women aged 20 to 39 who are married or divorced, have children, and work in professional, agricultural, or entrepreneurial fields. Data was collected through structured Likert scale questionnaires, validated by experts, and tested for reliability using Cronbach’s Alpha (>0.70). Statistical analysis was done with SPSS, including normality tests and regression. The results show that while women's economic contributions are important for family well-being, they do not significantly predict the intensity of dual roles (p = 0.682). Instead, factors like partner support, number of children, job demands, and cultural expectations have a greater impact. The study concludes that women's dual roles are shaped by the interaction of economic, social, psychological, and cultural factors. Policy implications stress the need for supportive family systems, flexible work arrangements, affordable child care, and cultural change to reduce the burden of dual roles and promote gender equality.